Haemoglobin Porto Alegre in a Cuban family. Issue 6 (December 1977) - Martínez, G; Lima, F; Wade, M; Estrada, M; Colombo, B; Heredero, L; Granda, H
Abstract : During a screening programme for abnormal haemoglobins in Habana, one case of Hb Porto Alegre was found in 23 000 cases analysed. The ability of this variant to polymerise in vitro and the absence of clinical features in the carriers have been confirmed. These observations are now explained by the findings of high levels of glutathione in the red cells of subjects heterozygous for Hb Porto Alegre: it is suggested that the increase of glutathione is responsible for the absence of in vivo polymerisation and accounts for the lack of clinical symptoms.